A new general iterative methods for solving the equilibrium problems, variational inequality problems and xed point problems of nonexpansive mappings: Ekkarath Thailert, R. Wangkeeree, Pakkapon Preechasilp - Team, Support (Thai Journal of Mathematics, 2016)
In this paper, we introduce the new general iterative methods for nding a common solutionset of equilibrium problems and the set of xed points of nonexpansive mappings which isa solution of a certain optimization problem related to a strongly positive linear operator.Under suitable control conditions, we prove the strong convergence theorems of such iterativescheme in a real Hilbert space. The main result extends various results existing in the currentliterature.